2004
DOI: 10.1523/jneurosci.5116-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Subunit Composition and Alternative Splicing Regulate Membrane Delivery of Kainate Receptors

Abstract: Kainate receptors (KARs) are heteromeric ionotropic glutamate receptors (GluRs) that play various roles in the regulation of synaptic transmission. The KAR subunits GluR5 and GluR6 exist under different splice variant isoforms in the C-terminal domain (GluR5a, GluR5b, GluR5c, GluR6a, GluR6b). The differential role of KAR subunit splice variants is presently unknown. In transfected COS-7 cells and neurons from wild-type and GluR5 ϫ GluR6 mice, we have found that the subcellular localization and membrane deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
99
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(111 citation statements)
references
References 44 publications
11
99
1
Order By: Relevance
“…We observed that, when expressed in COS-7 cells, myc-KRIP6 or CFP-KRIP6 are typically either diffuse (~60% of cells) or clustered in a perinuclear pattern (~40% of cells). On the other hand, GluR6 expressed alone in COS-7 cells shows a distribution (Fig 2A) consistent with Golgi network and plasma membrane, as previously described (Jaskolski et al, 2004;Yan et al, 2004). When CFP-KRIP6 and GluR6 were expressed together, in 88 % of cells where CFP-KRIP6 was clustered, GluR6 assumed a clustered perinuclear pattern and colocalized with CFP-KRIP6 ( Fig.…”
Section: Krip6 Interacts With Glur6 In Mammalian Expression Systems Asupporting
confidence: 84%
See 1 more Smart Citation
“…We observed that, when expressed in COS-7 cells, myc-KRIP6 or CFP-KRIP6 are typically either diffuse (~60% of cells) or clustered in a perinuclear pattern (~40% of cells). On the other hand, GluR6 expressed alone in COS-7 cells shows a distribution (Fig 2A) consistent with Golgi network and plasma membrane, as previously described (Jaskolski et al, 2004;Yan et al, 2004). When CFP-KRIP6 and GluR6 were expressed together, in 88 % of cells where CFP-KRIP6 was clustered, GluR6 assumed a clustered perinuclear pattern and colocalized with CFP-KRIP6 ( Fig.…”
Section: Krip6 Interacts With Glur6 In Mammalian Expression Systems Asupporting
confidence: 84%
“…In particular, given that the KRIP6 binding site (residues 842-899; Fig. 1) overlaps an identified forward trafficking determinant in GluR6 (residues 872-880; (Jaskolski et al, 2004;Yan et al, 2004), it seemed a likely possibility that KRIP6 might alter surface trafficking of GluR6. To test this idea, we determined whether KRIP6 changes surface levels of co-expressed GluR6 in both COS-7 cells and in hippocampal neurons.…”
Section: Krip6 Does Not Alter Surface Trafficking Of Glur6mentioning
confidence: 99%
“…Indeed, our antibody-based detection assays would not differentiate between KA2 proteins in monomeric, dimeric, or tetrameric assemblies, and therefore much of the total KA2 protein we detect in these assays could be in immature forms. Finally, GluR5-2b and GluR5-2c receptors, both of which are largely retained in the ER via argininebased determinants (6,19), did not associate with COPI at a detectable level, suggesting that other retention/retrieval pathways exist for these receptors.…”
mentioning
confidence: 92%
“…For example, GluR6a KAR subunits contain a forward trafficking determinant in their cytoplasmic tail and therefore are highly expressed as homomeric receptors on the plasma membrane of heterologous cell lines (3), whereas the KA2 subunit has an endoplasmic reticulum (ER) retention/retrieval signal and consequently does not reach the plasma membrane in the absence of other KAR subunits (4). The KA2 ER retention/retrieval signal consists primarily of an arginine-rich domain similar to that characterized on several other ionotropic glutamate receptor subunits, including NR1 (5) and GluR5-2c (6), as well as other signaling proteins such as ATP-sensitive potassium channels (K ATP ) (7) and GABA B receptors (8). Although a number of trafficking motifs in KAR subunits have been identified (9), little is known about how these trafficking signals control localization of receptors and which chaperone proteins are responsible for the modulation of receptor trafficking.…”
mentioning
confidence: 99%
“…These domains are particularly important in the control of receptor egress from the endoplasmic reticulum (ER) after receptor assembly. A number of critical ER-trafficking determinants have been identified in glutamate receptor subunits, which include argininerich sequences in NR1, GluR5-2b, GluR5-2c, GluR6, and KA2 subunits that promote ER retention/retrieval (12)(13)(14)(15)(16) or export (16,17), PDZ binding domains in GluR2 AMPA receptor subunits and splice variants of NR1 that control ER export (12,13,18), and juxtamembrane determinants that promote export of NR2B (19) and GluR␦2 (20) but retention of GluR2 subunitcontaining receptors (18). In addition to cytoplasmic determinants, glutamate receptors in the ER are subject to a resident quality control system that verifies that the proteins are properly folded and assembled before export to Golgi compartments (21).…”
mentioning
confidence: 99%